THE FACTORS RELATED TO THE APPLICATION OF CONTRACEPTION METHOD OF WOMEN OPERATION (MOW) - Zulfajri Rahman; Firdaus J Kunoli; Finta Amalinda (Promotif : Jurnal Kesehatan Masyarakat, 2017)
Based on the data of Family Planning Field Officer in South Palu sub district in 2014, 10,138 women of childbearing age (WUS) were women aged ≥ 35 years old using women's method of contraception (MOW) as many as 439 women of childbearing age. The purpose of this study is to determine the factors associated with the use of contraceptive methods of women's surgery (MOW) in Kecamatan Palu Selatan. The design of this study is an analytical survey of cross sectional study approach. The population in this study were fertile couples aged ≥ 35 years amounted to 99 respondents. The analysis used in this research is univariate and bivariate analysis with chi-square test. The results of this study indicate that there is no correlation between knowledge with use of contraception method of operation of woman (MOW) with value p = 0,981 (p = 0,05), there is no correlation between education with use of contraception method operation woman (MOW) with value p = 0.604 (p = 0.05), there was a relationship between husband support and contraceptive use of female operation method (MOW) with p = 0,009 (p = 0,05). This research suggests that people can know and understand the usefulness in the use of contraceptive methods of women's surgery (MOW).Keywords              : Contraception, application of contraception Mow, method of women operation